INDEKS KEPUASAN PENGGUNA E-LEARNING DENGAN MENGGUNAKAN MODEL END USER COMPUTING SATIFICATION (EUCS) - Tamba, Iventura Fitra Uli (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2020)
End user Computing Satisfaction is an overall evaluation of the information system used by system users in connection with the user experience of the information system. The user experience of the information system is measured to find out whether the information system used is effective and as desired. This study aims to determine the level of student satisfaction in using the e-learning system in the Management Study Program of STMB Multi Smart so that it can make improvements for the sake of maximizing the teaching and learning process. The population in this study were all 160 students of the management study program. From this population, 115 respondents obtained the e-learning user satisfaction index. From the research it was found that the majority of respondents (57.4%) were satisfied and 31.3% of respondents said they were very satisfied in using the e-learning system. From these results it can be concluded that the e-learning system has been able to meet the needs of students in the online learning process. Keywords: e-learning, End user computing satisfaction, user satisfaction